A general synthetic route to isomerically pure functionalized rhodamine dyes. (14th October 2015) - Mudd, Gemma; Pi, Irene Pérez; Fethers, Nicholas; Dodd, Peter G; Barbeau, Olivier R; Auer, Manfred
Abstract: A well-documented obstacle in the synthesis of functionalized rhodamine dyes is the generation of regioisomers which are difficult to separate. These isomers occur due to the use of unsymmetrical anhydride reagents, which possess two potential points of reactivity where condensation with meta-aminophenols can take place. In this report we describe a method which eliminates this problem by using phthalaldehydic acids as anhydride replacements. These reagents provide only one point of reactivity for the aminophenol, thus allowing direct access to single isomer tetramethylrhodamines and avoiding isomer generation altogether. A range of functionalities are shown to be tolerated at the 5- and 6-position of the dye compounds which are prepared in up to gram quantities using our method. The scope of the method is further demonstrated by the preparation of additional rhodamine family members Rhodamine B and X-Rhodamine.